Total Economic Value of Mangrove Forest in Pangkah Kulon and Pangkah Wetan Village Areas, Ujungpangkah District, Gresik Regency, East Java Province - Nyoto Santoso; Rizki Praba Nugraha; Ricardo Andalas (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Mangrove ecosystems have enormous benefits for the community, especially for people living on the coast. The problems in the management of mangrove forests in Pangkah Kulon and Pangkah Wetan Villages are people did not consider the importance of mangrove ecosystems in terms of economics. The purpose of this study is 1) analysis community perceptions of the mangrove ecosystem; 2) estimating the total economic value of the mangrove ecosystem in Pangkah Kulon and Pangkah Wetan Villages. Data analysis in this study used descriptive and quantitative analysis. Descriptive analysis is used to explain the activity of utilizing mangrove ecosystem resources, while quantitative analysis is used to calculate the perceptions and total economic value of mangrove ecosystems. The method of selecting respondents was purposive and snowball sampling, with a total number of respondents 60 person. Perception analysis using a Likert scale, analysis of the total economic value for the direct-use value using the price of resources used, indirect-use value using replacement costs, and option value using benefit transfers. The average perception of respondents has a value between 3.60 to 4.60, this mean that respondents agree and strongly agree to the functioning of mangrove ecosystems, both in economic, socio-cultural, ecological and physical functions, and respondents have a high dependency on mangrove resources. Analysis of the potential total economic value of the mangrove ecosystem is Rp. 97,547,237,496/year. The total economic value obtained from the direct-use value (utilization of the fisheries sector) amounted to Rp. 51,672,497,300/year, indirect-use value (abrasion restraints and sea waves) amounted to Rp. 45,161,544,004/year, and option value (biodiversity) amounted to Rp.713,196,192/year. The total economic value of the mangrove ecosystem in Pangkah Kulon and Pangkah Wetan Villages shows that the mangrove ecosystem provides great benefits for the community. Keywords: direct-use value, existence value, indirect-use value, mangrove ecosystem, option value, total economic value